Internalization of Religious Moderation through Islamic Religious Education in the Era of Globalization (IJORER : International Journal of Recent Educational Research, 2026)
This study aims to analyze the internalization of religious moderation at SMA Muhammadiyah 1 Gresik as a response to fostering a harmonious life and preventing division within the educational environment. This study uses a descriptive qualitative approach was used. The data were collected through interviews, observations, and documentation. Validity was ensured using source and technique triangulation. Data analysis was conducted in three stages, namely data collection, data presentation, and drawing conclusions based on the findings obtained in the field. The result of this study indicates that Internalization of religious moderation through Islamic Religious Education at SMA Muhammadiyah 1 Gresik aligns with the school's needs, as reflected in the nationally standardized indicators of religious moderation and the principles of Risalah Islam Berkemajuan, namely tolerance, non-violence, national commitment, adaptability to local culture, and dynamization. Internalization is carried out through three core processes: externalization, objectification, and subsequent internalization. The findings of this study also underscore the strategic role of private schools through their curricula, learning processes, and the exemplary conduct of educators in supporting government policies on the implementation of moderation in schools. The implementation of this research is the strategic formation identified in this study can serve as a reference for schools in internalizing religious moderation based on the indicators of religious moderation and the principles of Risalah Islam Berkemajuan which emphasizes a locally based approach, with the city of Gresik serving as a representative model of a multicultural city an approach that has not been widely adopted in previous studies.